2022
DOI: 10.3390/met12101605
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Machining Conditions on Temperature and Vickers Microhardness of Chips during Planing

Abstract: For the machining of long and narrow surfaces and when processing multiple pieces, planing technology is used, the productivity of which can be higher than that of milling, although it is relatively slow machining. The article aims to study the degree of influence of the geometry of the tool (the angle of cutting-edge inclination and the angle of the tool-orthogonal rake), as well as the cutting conditions (cutting depth and cutting speed) on the chip characteristics (temperature and microhardness) in orthogon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 36 publications
(36 reference statements)
0
5
0
Order By: Relevance
“…The formation of machined surface microhardness of titanium alloy Ti-6Al-4V is the subject of studies by Hou with Li [25] as well as Mathoho and coworkers [26]. Monka and colleagues [27] considered the influence of cutting modes and tool geometric parameters on the microhardness of the machined surface in orthogonal and oblique cutting. They obtained response surfaces and correlation dependences of microhardness on the above-studied parameters.…”
Section: Brief Description Of the State Of The Art On The Determinati...mentioning
confidence: 99%
“…The formation of machined surface microhardness of titanium alloy Ti-6Al-4V is the subject of studies by Hou with Li [25] as well as Mathoho and coworkers [26]. Monka and colleagues [27] considered the influence of cutting modes and tool geometric parameters on the microhardness of the machined surface in orthogonal and oblique cutting. They obtained response surfaces and correlation dependences of microhardness on the above-studied parameters.…”
Section: Brief Description Of the State Of The Art On The Determinati...mentioning
confidence: 99%
“…The main papers take a materials-focus perspective utilizing various manufacturing processes, such as turning [5,13], planing [10] and electric discharge machining [3,15]. A review paper reported on the basic categories of leaded and lead-free machinable brass…”
Section: Contributionsmentioning
confidence: 99%
“…The Special Issue "Machinability and Tribological Performance of Advanced Alloys" contains fifteen research articles [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15], including one review paper [5]. The contents of this collection cover a wide spectrum of cross-disciplinary fields related to the machinability and tribological behaviour of materials with a variety of industrial applications.…”
Section: Contributionsmentioning
confidence: 99%
See 2 more Smart Citations